2014
DOI: 10.3109/0886022x.2014.926216
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin secretion is impaired in women with preeclampsia and an abnormal circadian blood pressure rhythm

Abstract: Non-dipping circadian blood pressure (BP) is a common finding in preeclampsia, accompanied by adverse outcomes. Melatonin plays pivotal role in biological circadian rhythms. This study investigated the relationship between melatonin secretion and circadian BP rhythm in preeclampsia. Cases were women with preeclampsia treated between January 2006 and June 2007 in the University Hospital of Larissa. Volunteers with normal pregnancy, matched for chronological and gestational age, served as controls. Twenty-four h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 53 publications
5
16
0
2
Order By: Relevance
“…The result in the current study showed that all (20)healthy pregnant women have the physiological rhythm of BP and normal levels of plasma melatonin secretion at daytime and nighttime measurement , while 20 women with preeclampsia were of two groups , the dipping group were have the normal physiological rhythm of BP and melatonin secretion of daytime and nighttime melatonin secretion , the second or nondipping group the BP did not show the normal nocturnal dipping and nocturnal melatonin secretion was decreased of daytime and nighttime compared to normal healthy pregnant women and dipping group with PE . This is concordant with that revealed by Bouchlariotou et al2014 (23) whom study included 51 women that measuring serum and urine melatonin levels ,20 women of normal healthy pregnancy all were dipper with normal melatonin secretion and 31 women with preeclampsia, women with preeclampsia (68%) non-dipper with reduced nighttime melatonin secretion (P value< 0.001) compared to normal healthy pregnant women , and (32%) were dippers with normal rhythm of BP and daytime , nighttime melatonin secretion. Also concordant with that revealed by Nakamura et al 2001 (23),study showed serum melatonin secretion in preeclampsia significantly lower than serum melatonin secretion of normal pregnant women after 32 weeks of gestation .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The result in the current study showed that all (20)healthy pregnant women have the physiological rhythm of BP and normal levels of plasma melatonin secretion at daytime and nighttime measurement , while 20 women with preeclampsia were of two groups , the dipping group were have the normal physiological rhythm of BP and melatonin secretion of daytime and nighttime melatonin secretion , the second or nondipping group the BP did not show the normal nocturnal dipping and nocturnal melatonin secretion was decreased of daytime and nighttime compared to normal healthy pregnant women and dipping group with PE . This is concordant with that revealed by Bouchlariotou et al2014 (23) whom study included 51 women that measuring serum and urine melatonin levels ,20 women of normal healthy pregnancy all were dipper with normal melatonin secretion and 31 women with preeclampsia, women with preeclampsia (68%) non-dipper with reduced nighttime melatonin secretion (P value< 0.001) compared to normal healthy pregnant women , and (32%) were dippers with normal rhythm of BP and daytime , nighttime melatonin secretion. Also concordant with that revealed by Nakamura et al 2001 (23),study showed serum melatonin secretion in preeclampsia significantly lower than serum melatonin secretion of normal pregnant women after 32 weeks of gestation .…”
Section: Discussionsupporting
confidence: 89%
“…This is concordant with that revealed by Bouchlariotou et al2014 (23) whom study included 51 women that measuring serum and urine melatonin levels ,20 women of normal healthy pregnancy all were dipper with normal melatonin secretion and 31 women with preeclampsia, women with preeclampsia (68%) non-dipper with reduced nighttime melatonin secretion (P value< 0.001) compared to normal healthy pregnant women , and (32%) were dippers with normal rhythm of BP and daytime , nighttime melatonin secretion. Also concordant with that revealed by Nakamura et al 2001 (23),study showed serum melatonin secretion in preeclampsia significantly lower than serum melatonin secretion of normal pregnant women after 32 weeks of gestation . Also concordant with that revealed by Zeng et al2016 (26), serum was collected from women with preeclampsia the serum levels of melatonin were significantly reduced in women with preeclampsia at presentation , while its inconsistent with Tranquilly et al 2004 (27),study of 16 primigravidae showed the rhythm of melatonin secretion was lost in all pregnant women with lost of blood pressure rhythm and preeclamptic women have higher melatonin concentrations (P value<0.001) , this may be due to small sample size and in present study we carefully selected patient ages (20-30) because melatonin secretion is age-related secretion that higher levels in children and the lower levels in elderlies and to avoid age-related differences we selected age ranges between (20 -30) years old .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…There is a decrease in placental α7nAChR mRNA and protein in women with preeclampsia [110], indicating that this would be correlated with the decrease in placental melatonin production that is also evident in this condition [111]. Preeclampsia is also associated with a decrease in pineal melatonin, which may be especially evident in preeclamptic women with non-dipping nighttime blood pressure [112]. Melatonin's positive regulation of the α7nAChR may also directly regulate obesity, since α7nAChR agonism is associated with decreased food intake [113].…”
Section: Melatonin and The Alpha 7 Nicotinic Receptormentioning
confidence: 99%